Workshop Menyusun Asesmen Formatif Menggunakan Aplikasi Berbasis Game untuk Mahasiswa Fakultas Pendidikan - Anggeraini, Nining; Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Fajri, Ahmad Syamsul; Tahir, Muhammad (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2025)
This article reports on a community engagement initiative in the form of a workshop designed to strengthen the pedagogical competence of students in the faculty of education, specifically in creating formative assessments through game-based applications. The workshop incorporated principles of Transformative Learning and Experiential Learning, utilizing qualitative instruments such as questionnaires and project documentation. The program effectively shifted students’ perspectives on assessment, with notable progress in their ability to design interactive and pedagogically sound quizzes. Despite some variation in creative design and video tutorial presentation skills, the overall outcomes were positive. The workshop is expected to make a meaningful contribution to enhancing both the quality of learning and participants’ pedagogical skills in developing and applying formative assessments using interactive quiz tools.